Manajemen Laba Setelah Perubahan Peringkat Obligasi Perusahaan - Sijabat, Deviana; Eka Damayanthi, I Gst Ayu (E-Jurnal Akuntansi; Vol 28 No 3 (2019), 2019)
This study aims to obtain empirical evidence of earnings management after changes in corporate bond ratings. The modified Jones model is used to identify companies that practice earnings management. The population in this study is all bonds of nonfinancial companies that issue bonds and those that experience upgrades or downgrades of bond ratings in the period 2010-2016. The method of determining the sample in this study used purposive sampling to obtain 30 samples of companies that experienced upgrades or downgrades. Hypothesis testing uses the One Sample T Test. The conclusion of this study is that the bond issuing company carries out earnings management that increases profits after the bond rating has undergone an upgrade or a downgrade. Keywords: Earnings Management, Bond Ratings, Discretionary Accruals